The Role of Corporate Communications Toward PT. Freeport Indonesia's Branding in Changing the Public Perceptions - Steven Paoh, Spencer; Ashari Nasution, Reza (The Indonesian Journal of Business Administration, 2017)
Abstract - PT. Freeport Indonesia is a subsidiary of Freeport-McMoRan Inc. (FCX) which has the largest copper and gold reserves in the world located in Mimika Regency, Papua. There is ongoing negotiations between the government and PT Freeport Indonesia regarding the guarantee of the company's operational continuity. This negotiation is very important for both parties to determine whether PTFI can continue to operate and provide benefits to our Nation or have to stop because it is considered not to contribute to our Country. Public opinion is very influential in the process of reaching the agreement, which discusses some items that one of them and most importantly for the company about obtaining contract extension certainty until 2041. The Indonesian public is less aware of PT Freeport Indonesia's gait, especially its positive action. The press in Indonesia generally does not pay attention to the role of PT Freeport Indonesia, especially the positive side. The role of the mainstream mass media in shaping public opinion has begun to be eroded by other forces, namely social media and public opinion in Indonesia tend to follow public opinion, although the general opinion is not in line with reality. In this thesis the authors want that through some communication strategy done will be able to make people can see PT Freeport Indonesia better based on the facts that exist, on the positive things that have been done so that negative opinions that have been formed Can gradually be positive. This thesis is an early scientific effort to determine the right communication strategy to change public perception and strengthen the branding of PT Freeport Indonesia. The communication and branding strategies must be applied continuously to obtain maximum results for PT Freeport Indonesia.Keywords: Certainty of Contract Extension, Public Opinion, Operation Continuity, communication Strategy